Retail sector distribution chains for malaria treatment in the developing world: a review of the literature - Hanson Kara G (Malaria Journal, 2010)
Abstract Background In many low-income countries, the retail sector plays an important role in the treatment of malaria and is increasingly being considered as a channel for improving medicine availability. Retailers are the last link in a distribution chain and their supply sources are likely to have an important influence on the availability, quality and price of malaria treatment. This article presents the findings of a systematic literature review on the retail sector distribution chain for malaria treatment in low and middle-income countries. Methods Publication databases were searched using key terms relevant to the distribution chain serving all types of anti-malarial retailers. Organizations involved in malaria treatment and distribution chain related activities were contacted to identify unpublished studies. Results A total of 32 references distributed across 12 developing countries were identified. The distribution chain had a pyramid shape with numerous suppliers at the bottom and fewer at the top. The chain supplying rural and less-formal outlets was made of more levels than that serving urban and more formal outlets. Wholesale markets tended to be relatively concentrated, especially at the top of the chain where few importers accounted for most of the anti-malarial volumes sold. Wholesale price mark-ups varied across chain levels, ranging from 27% to 99% at the top of the chain, 8% at intermediate level (one study only) and 2% to 67% at the level supplying retailers directly. Retail mark-ups tended to be higher, and varied across outlet types, ranging from 3% to 566% in pharmacies, 29% to 669% in drug shops and 100% to 233% in general shops. Information on pricing determinants was very limited. Conclusions Evidence on the distribution chain for retail sector malaria treatment was mainly descriptive and lacked representative data on a national scale. These are important limitations in the advent of the Affordable Medicine Facility for Malaria, which aims to increase consumer access to artemisinin-based combination therapy (ACT), through a subsidy introduced at the top of the distribution chain. This review calls for rigorous distribution chain analysis, notably on the factors that influence ACT availability and prices in order to contribute to efforts towards improved access to effective malaria treatment.